AKIBAT HUKUM PENYELENGGARAAN PENGANGKUTAN BARANG OLEH PENGANGKUT DALAM KEADAAN MEMAKSA (OVERMACHT) - Parama Iswara, I Gede (Kertha Semaya : Journal Ilmu Hukum, 2015)
This paper is titled “The Legal Result of Goods Transporter Conduction by Carrier in the Event of Force Majeur (Overmacht)”. Background of this paper is every goods transporter conduction commonly is discharged from obstacles that cause by force majeur event. The purpose of this paper is to know the carrier responsibility in conduction of goods transporter and legal result of goods transporter conduction by carrier in the event of force majeur. In this paper, it is used normative legal research analysis which try to solve the problems rooted by the literatures and statutes. The conclusion of this paper is the carrier shall be conducted the transporter properly while maintaining the goods safely and also there are two theory about problem solve in the conduction of goods transporter related force majeur event, subjective and objective theory.
Keywords: Legal Result, Goods Transporter, Force Majeur